2008
DOI: 10.14295/rbho.v14i1.225
|View full text |Cite
|
Sign up to set email alerts
|

Potencial de mercado de Bastão-do-impera.

Abstract: O incremento da produção de flores tropicais é de grande importância para a Floricultura nacional. Espécies do gênero <i>Etlingera e Zingiber spectabile</i> são exemplos de flores tropicais exóticas que apresentam características interessantes para comercializá-las como flores de corte. O potencial de mercado para estas espécies no Brasil conduz à análise dos aspectos positivos e negativos em relação à produção, pós-colheita e comercialização destas culturas, objetivos deste artigo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…However, there was an effect on LI and SD, where it is observed that the plants from the RIZ implantation system showed higher values (Table 2). The characteristics required for commercialization of a type A floral stem (of better quality) of the Ginger Torch is at least 80 cm in length and 10 mm in diameter (Loges et al, 2008). Therefore, it is possible to affirm that all treatments produced inflorescences with the dimensions (length and diameter of the stem) that meet the requirements for the commercialization of type A stems.…”
Section: Ndet Ndei Ndhmentioning
confidence: 97%
See 1 more Smart Citation
“…However, there was an effect on LI and SD, where it is observed that the plants from the RIZ implantation system showed higher values (Table 2). The characteristics required for commercialization of a type A floral stem (of better quality) of the Ginger Torch is at least 80 cm in length and 10 mm in diameter (Loges et al, 2008). Therefore, it is possible to affirm that all treatments produced inflorescences with the dimensions (length and diameter of the stem) that meet the requirements for the commercialization of type A stems.…”
Section: Ndet Ndei Ndhmentioning
confidence: 97%
“…From the beginning of the emission of floral stems, each stem was marked, and the date of emission was noted. And the harvest was performed when the inflorescences reached the E stage (lower bracts open, central part semiopen) (Loges et al, 2008). The inflorescences were always harvested in the morning and then sent to the laboratory to measure the length of the floral stem (LFS), considering the distance between the base of the pseudo stem and the apex of the inflorescence (cm); length of the inflorescence (LI), distance between the colored part of the peduncle and the apex of the inflorescence (cm); and stem diameter (SD), 20 cm below the inflorescence (mm), using a digital caliper.…”
Section: Growth and Phenologymentioning
confidence: 99%
“…In northeastern of Brazil, it is cultivated with inflorescences varied coloring, for exemple, in white pink color called porcelain pink color, in darker pink color Pink Torch and red color Red Torch (Loges et al, 2008) tulipa.…”
Section: Introductionmentioning
confidence: 99%
“…Essa espécie destaca-se por seu porte exuberante e formas exóticas de suas grandes inflorescências cerosas com várias colorações, desde branca até o vermelho, incluindo vários tons de rosa. Apresenta características interessantes que levaram vários produtores a comercializá-lo como flor de corte, para composição de arranjos florais e como planta para paisagismo (LOGES, 2008;RIBEIRO et al, 2012).…”
Section: Introductionunclassified